Translational research on rapid steroid actions - Wendler, Alexandra; Wehling, Martin (Steroids, 2010)
Translational research is a burgeoning science that shows potential to improve the transition of research from bench to bedside. This novel science explores all major aspects of preclinical and clinical issues which are relevant for the success of translational pharmaceutical or medical device/diagnostic innovations. This includes target risk assessment, biomarker evaluation and predictivity grading both for efficacy and toxicity, early human trial design adequate to guide stop/go decisions on grounds of biomarker panels, and biostatistical methods to analyze multiple readout situations and quantify risk projections. Representing a comparably novel science, rapid steroid actions have been recognized to carry potential clinical implications in various fields. Findings in this field have not yet been successfully translated into clinically relevant new medicines except for neurosteroids. A promising compound is the membrane estrogen receptor agonist STX, which may be applicable for estrogen withdrawal symptoms. Nongenomic vitamin D analogs may be useful as antiinflammatory, anticancer or diabetes preventing agents. Further the membrane thyroid receptor agonist tetrac may be useful in cancer treatment. Unfortunately lazaroids (membrane-only active glucocorticoids), which have been clinically tested as neuroprotective agents, had to be abandoned because of lacking clinical efficacy. Yet, the hierarchy of antirheumatic glucocorticoid action in regard to their clinical potency may better correlate with their membrane effects than their ability to bind to the classic glucocorticoid receptor. To improve the translational success of the rapid actions of steroids research, scientists should become familiar with major aspects of translational work and always seek for translational dimensions in their research.
Gesehen am 03.11.2023